Temporal and spatial changes of macrobenthos communities in south east shores of the Caspian sea (Nexo Revista Científica, 2021)
In this research, Sampling of macrobenthos of Mazandaran beaches was performed in 7 stations at two depths of 5 and 10 meters during four seasons in 2020 using a grab with 8 replications in each station. In this study, a total of 10472 individuals were counted, which belonging to 22 species from 13 families. The highest frequency of macrobenthos (648 ± 170.79) was observed in spring and the highest amount of biomass (36.21 ±2.5 gr / m2) was observed in winter. Moreover, the highest prevalence of macrobenthos predominant groups during the sampling period was observed in Bivalves (40%), Crustaceans (36%), Annelids (22%) and Gastropoda (2%), respectively.  The results of PERMANOVA analysis showed that the effect of two factors of season and depth impacted the biomass, abundance, species richness, species composition and community structure of macrobenthos significantly. Furthermore, the results showed that with increasing the depth from 5 to 10 meters, macrobenthos abundance increased by 4, 2, 1 and 9 times in spring, summer, autumn and winter, respectively. Moreover, increase in depth from 5 to 10m, the values of biomass and species richness have increased. In according to these results, it can be concluded that biomass and diversity index of macrobenthos communities change considerably in different seasons and depths. Therefore, natural changes of these variables should be considered when using these macrobenthos communities to assess the impact of environmental factors.